The opportunities and challenges of adopting ChatGPT in medical research - Alsadhan, Abeer; Al-Anezi, Fahad; Almohanna, Asmaa; Alnaim, Norah; Alzahrani, Hayat; Shinawi, Reem; AboAlsamh, Hoda; Bakhshwain, Amal; Alenazy, Maha; Arif, Wejdan; Alyousef, Seham; Alhamidi, Sami; et al. (Frontiers in Medicine, 2023)
Purpose: this study aims to investigate the opportunities and challenges of adopting ChatGPT in medical research.Methods: A qualitative approach with focus groups is adopted in this study. A total of 62 participants including academic researchers from different streams in medicine and eHealth, participated in this study.Results: A total of five themes with 16 sub-themes related to the opportunities; and a total of five themes with 12 sub-themes related to the challenges were identified. The major opportunities include improved data collection and analysis, improved communication and accessibility, and support for researchers in multiple streams of medical research. The major challenges identified were limitations of training data leading to bias, ethical issues, technical limitations, and limitations in data collection and analysis.Conclusion: Although ChatGPT can be used as a potential tool in medical research, there is a need for further evidence to generalize its impact on the different research activities.